MENGGUNAKAN KARTU KATA UNTUK MENINGKATKAN PENGUASAAN ATURAN PERUBAHAN NADA â€œYIâ€ DAN â€œBUâ€ DI SMA - Pasaribu, Susi Lestari; Ina, Ina; Kion, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractTone is very important in Mandarin, because the tone has the benefit of distinguishing meaning. Mandarin has four tones, and under certain conditions some characters will experience tone changes, for instance tone change of "yi" and "bu". Therefore, students who forget the rules of change of tone will often be wrong in reading it. Therefore, the author used card as media to improve the mastery of the change of tone "yi" and "bu" in the students of class XI Mipa 2 and Mipa 3 of SMA Gembala Baik. Based on the data obtained from the pre-test and post-test, the percentage of students' correctness in working on the problem has increased for 45.5% in multiple using cards is choice and 31% in pronouncing the tone change. The used card as media has proved effective in improving the mastery of the "yi" and "bu" tone changes. For the word "yi", the common mistake was the changing of the first tone to the fourth tone. Meanwhile for word "bu" on the four note meets a four note. The cause of this mistake was  students were often to read the tone using the real tone. Keywords: Tone, Changes tone, ? yi?, ?bu?